Reasons for Leaving School and Alcohol Use Among Out of School Youth in South Africa. (6th August 2019) - Desai, Rachana; Mercken, Liesbeth; Ruiter, Rob; Schepers, Jan; Reddy, Priscilla
After students drop out of school, their alcohol use may vary according to the reason for dropping out. In this paper, out of school youth (OSY) are those between 13–20 years old, have not completed their schooling, and have not enrolled in secondary or high school for the current academic year. OSY are at heightened risk of alcohol use. This study examined the relationship between reasons for leaving school and alcohol use, taking into account gender differences. Survey data from 4222 OSY (mean age = 17.4 years, SD = 1.9; males = 59.4%) were analysed using ordinal regression. Leaving school for "not having enough money to pay for school fees" was associated with more alcohol consumption, among females living specifically in rural areas of Gauteng. However, in urban areas of Kwazulu Natal and Mpumalanga, females who left school for the same reason as their rural counterparts were less likely to consume alcohol in the past month. Males were more likely to consume higher levels of alcohol if they reported leaving school due to making someone pregnant, but only when they resided in peri-urban areas. Understanding the relationship between reasons for leaving school and alcohol use may give us insight into the profile of school dropouts at risk for alcohol use. This information is useful for intervention development across the school, home and community.